Sa’di and Fakhr-al-Din Abu-Bakr Hawayeji - Javad Bashari (تاریخ ادبیات)
Fakhr-al-Din Abu-Bakr b. Abu-Nasr Hawayeji was the bārbak and prime minister of Atabak Abu-Bakr b. Sa’d b. Zangi, the powerful ruler of Fars from the Salghori family. He is one of the prominent political, military, and cultural figures in the vast territory of Fars in the first half of the 7th century AH/ 13th century, and part of Sa’di’s life coincided with his period of authority. Sa’di praised Fakhr-al-Din in the preface of Golestan and perpetuated his name, and addressed him in two less-examined parts of his Kolliyāt. These two parts have always been a matter of doubt, but now, based on reliable old documents, we can clarify them. What previously Mohammad Qazvini had doubted was a short elegy in which a historical contradiction was found about the life of Fakhr-al-Din, the Salghori minister and ruler; it was not clear whether this elegy was for him or someone else. Now we can undoubtedly elucidate that Sa’di composed the elegy not for him but the death of his son. In another part of this article, important historical information about this minister is presented; some was extracted from historical sources and some taken from poets’ Divans